Efficient pseudonym certificate distribution scheme for Internet of vehicles based on novel sanitizable multi-signature - LIU Zhaoman; YANG Yafang; NING Jianting; ZHAO Yunlei (Tongxin xuebao)
Existing pseudonym certificate schemes fail to adequately address the collaboration needs of multiple entities in the certificate issuance process. To address this, a sanitizable multi-signature (SMS) scheme based on chameleon Hash (CH) and multi-signature (MS) was proposed. By introducing a sanitizability function, SMS scheme allowed authorized sanitizers to update signature data without interacting with the original signers, resolving the issue of rapid response when vehicles frequently change pseudonyms. To prevent the abuse of sanitizability privileges, SMS verified the source of multi-signatures to trace malicious sanitizability actions. Furthermore, the proposed scheme deployed the sanitizability function on road-side units (RSU) and proposed an efficient pseudonym certificate distribution scheme. Security analysis shows that the scheme effectively resists correlation and impersonation attacks, with minimal computational overhead on RSU and vehicles, ensuring good efficiency and security during pseudonym certificate and anonymous authentication processes.